Chronic inflammation markers are associated with risk of pancreatic cancer in the Swedish AMORIS cohort study. - Sollie, Sam.; Michaud, Dominique S.; Sarker, Debashis.; Karagiannis, Sophia N.; Josephs, Debra H.; Hammar, Niklas.; Santaolalla, Aida.; Walldius, Goran.; Garmo, Hans.; Holmberg, Lars.; Jungner, Ingmar.; Van Hemelrijck, Mieke. (Tufts University. Tisch Library., 2019)
Background: Nested case-control studies examining the association between serum markers of chronic inflammation, focused on three specific biomarkers (CRP, IL-8 and TNF-α), and risk of pancreatic cancer have reported no associations. In this study, we evaluated associations between standard pre-diagnostic serum markers of chronic inflammation (CRP, albumin, haptoglobin and leukocytes) and pancreatic cancer risk in the Swedish Apolipoprotein-related MORtality RISk (AMORIS) prospective cohort study.; Keywords: Chronic inflammation, Pancreatic cancer, CRP, Albumin, Haptoglobin, Leukocytes, AMORIS.; Springer Open.